2015
DOI: 10.2471/blt.14.142489
|View full text |Cite
|
Sign up to set email alerts
|

Introducing rapid diagnostic tests for malaria to drug shops in Uganda: a cluster-randomized controlled trial

Abstract: Objective To evaluate the impact – on diagnosis and treatment of malaria – of introducing rapid diagnostic tests to drug shops in eastern Uganda. Methods Overall, 2193 households in 79 study villages with at least one licensed drug shop were enrolled and monitored for 12 months. After 3 months of monitoring, drug shop vendors in 67 villages randomly selected for the intervention were offered training in the use of malaria rapid diagnostic tests and – if trained – offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 27 publications
4
43
0
Order By: Relevance
“…However, the current study examined the uptake and utilization of these health technologies once available. This is in line with another study [ 63 ] that reported that presence of diagnostics at the drug shops was necessary but not sufficient to translate into their uptake. Other researchers [ 63 , 64 ] have argued that behavioural change efforts and provider incentives are necessary.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the current study examined the uptake and utilization of these health technologies once available. This is in line with another study [ 63 ] that reported that presence of diagnostics at the drug shops was necessary but not sufficient to translate into their uptake. Other researchers [ 63 , 64 ] have argued that behavioural change efforts and provider incentives are necessary.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with another study [ 63 ] that reported that presence of diagnostics at the drug shops was necessary but not sufficient to translate into their uptake. Other researchers [ 63 , 64 ] have argued that behavioural change efforts and provider incentives are necessary. Hence, these findings infer that the iCCM intervention improved the appropriateness of drug seller treatment practices in the intervention arm as compared to the comparison arm.…”
Section: Discussionsupporting
confidence: 90%
“…The fact that most people who tested negative on the RDT decided to still take AL also suggests that patients may have lacked confidence in the RDT result. Though our study design is likely to have biased RDT-negative patients toward taking the medicines, several other studies, across different contexts, have also found high prescription and purchase rates of ACTs despite a negative test result, 28,[48][49][50] likely because there is a tendency in malariaendemic areas for both health workers and patients to treat all fever episodes as malaria. [51][52][53] It may be that over time, as patients learn about the accuracy of the test, RDTs will have a greater impact on adherence.…”
Section: Discussionmentioning
confidence: 96%
“…Although appropriate treatment is moderate (55%) in Nigeria [ 17 ] to high (80–99%) in Uganda [ 19 , 21 , 23 ], compliance with negative test results is low. Up to 32% of RDT negative cases in the Ghanaian [ 16 ], 37.4% [ 21 ] and 45% [ 20 ] in the Ugandan, and 51.6% in the Myanmar is studies [ 25 ] receive anti-malarial medicines. In the Tanzanian study [ 24 ], only 7% of the test negative cases received artemisinin-based combination therapy (ACT).…”
Section: Introductionmentioning
confidence: 99%